Study of Semantic Deviation in the Collection of The Flowers of Evil and Persian Translations - Mina Rezaei; Mitra Raissi Dehkordi; Youssef Aram (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Semantic deviation means the transgression of the criteria that determines the coincidence of the vocabularies and avoiding the standard of language. Based on the research findings, we could say that semantic deviation is an important factor in the creation of poetry. In this sense, the more frequent the occurrence of this type of deviation is, the more semantic horizons in the poetry are achieved, and the achievement of meaning occurs later. In Baudelaire’s poems, the creation of new and special compositions, picturing the details, imagination, making beautiful scenes, and using pleasant similes and metaphors, led to the emergence of this kind of semantic deviation. The aim of this article is to study the semantic deviation in The Flowers of Evil by Charles Baudelaire, referring to metaphor and metonymy, and their reflection in the translations by Hassan Honarmandi, Mohammad-Ali Eslami Nodooshan, and Mohammadreza Parsayar. To reach this goal, at first, we examined semantic deviation as an important issue in the critique of formalism, focusing on Geoffrey Leech’s classification, a formalist linguist, and then the original text has been compared with its translations, and the differences between them have been studied.